Nomogram predicting early neurological improvement in ischaemic stroke patients treated with endovascular thrombectomy. (6th October 2020) - Zhang, X.; Peng, M.; Feng, C.; Wang, H.; Gong, P.; Jiang, T.; Xie, Y.; Yang, D.; Yuan, K.; Chen, J.; Li, Y.; Liu, D.; et al.
Abstract : Background and purpose: Early neurological improvement (ENI) after endovascular thrombectomy (EVT) has been associated with favorable outcomes. This study aimed to identify the optimal definition of ENI and develop a nomogram for predicting ENI after EVT in acute ischaemic stroke. Methods: Patients with EVT were enrolled from a multicenter registry as the training cohort. The receiver operating characteristic curve was used to estimate the optimal threshold for ENI at 24 h of EVT. Logistic regression analysis was utilized to generate the best‐fit nomogram for predicting ENI. The discrimination of the nomogram was assessed using the area under the receiver operating characteristic curve (AUC). An additional 447 patients from two stroke centers were prospectively recruited as the test cohort for validating the nomogram. Results: A total of 612 patients with EVT were included in the training cohort. The optimal threshold for predicting 3‐month favorable outcome (modified Rankin Scale 0–2) was an improvement of the National Institutes of Health Stroke Scale (NIHSS) score by ≥6 points (AUC 0.875; sensitivity 79.5%; specificity 90.7%). Age, blood glucose, recanalization, symptomatic intracranial hemorrhage (sICH) and baseline Alberta Stroke Program Early Computed Tomography Score (ASPECTS) were independently associated with ENI, and were incorporated in the nomogram. The AUC of the nomogram was 0.795 in the training cohort and 0.752 in the test cohort. Conclusions: A reduction of NIHSS score ≥6 appeared to be the optimal definition of ENI. The nomogram composed of age, blood glucose, recanalization, sICH and baseline ASPECTS may predict the probability of ENI in ischaemic stroke patients treated with EVT. Abstract : Our study demonstrated that a reduction of the National Institutes of Health Stroke Scale score ≥6 appeared to be the optimal definition of early neurological improvement (ENI). A nomogram comprising age, blood glucose, recanalization, symptomatic intracranial hemorrhage and baseline Alberta Stroke Program Early Computed Tomography Score may predict the probability of ENI in ischaemic stroke patients treated with endovascular thrombectomy. The discrimination and calibration of the nomogram was further confirmed in external validation.